More Than a Pipeline Problem: Evaluating the Gender Pay Gap in Canadian Academia from 1996 to 2016 - Momani, Bessma; Dreher, Emma; Williams, Kira (Canadian Journal of Higher Education, 2019)
This article measures gender pay gaps in Ontario’s public post-secondary education sector from 1996 to 2016 using the Public Sector Salary Disclosure Data. We find gaps widening among all faculty ranks. Men were paid on average 2.06%, 2.14%, and 5.26% more than their women colleagues for all employees, university teaching staff, and deans, respectively. We also conduct a Blinder- Oaxaca decomposition to measure the source of gendered salary differentials. Pay gaps persist during this time period despite controlling for the literature’s most common explanations, including the “pipeline effect.” Our results additionally imply that women’s years of experience in academia do not mitigate the observed pay gaps. Suggestions for future research include increasing the scope of our study to factor in finer details such as labour productivity.